Anion recognition using meta-substituted ureidocalix[4]arene receptors - Surina, A; Čejka, J; Salvadori, K; Lhoták, P (Organic & biomolecular chemistry, 2024)
Calix[4]arenes bearing urea units at the meta position(s) of the upper rim of the macrocyclic skeleton were prepared by the reaction of the corresponding amines with aryl isocyanates. As shown by the 1H NMR and UV/vis titration experiments, these systems are capable of effectively complexing selected anions even in a highly competitive environment (such as DMSO-d6). While the monoureido derivatives showed approximately the same complexation ability irrespective of the substitution (para vs. meta isomers), the bisureas at the upper rim demonstrated interesting differences in complexation. The meta,meta and para,para isomers were shown to prefer 2 : 1 complexes (anion : receptor) regardless of the anion tested, while the analogous meta,para isomer formed 1 : 1 complexes with strongly coordinated anions (e.g. H2PO4-) based on synchronous complexation by both ureido groups. This suggests that the regioselective introduction of urea units into the upper rim of calix[4]arene brings with it the possibility of "tuning" the complexation properties depending on the substitution pattern of the functional groups.